ChemInform Abstract: Two‐Dimensional Antiferromagnetism in the [Mn3+xO7][Bi4O4.5‐y] Compound with a Maple‐Leaf Lattice. Issue 2 (9th January 2013) - Aliev, Almaz; Huve, Marielle; Colis, Silviu; Colmont, Marie; Dinia, Aziz; Mentre, Olivier
Abstract Black single crystals of Bi4Mn3O11.5 are obtained besides Bi6O8Cl from the solid state reaction of Bi2O3, BiOCl, PbO, and MnO2 (sealed Au tube, 1173 K, 12 h).